EMPOWERMENT OF AA MICRO BUSINESS IN DEVELOPING DIVERSICATION OF CAKE PRODUCTS IN SURABAYA - Dr. H. Zakariya, MS., MM.; Drs. Ec. Kunto Inggit Gunawan, MM.; Drs. Ec. Mataji, MM. (JPM17: Jurnal Pengabdian Masyarakat, 2020)
Since the enactment of the Asean Economic Community (AEC) at the end of 2015 should encourage all economic actors including SMEs and Micro Enterprises to improve themselves in order to improve the quality of production of both goods and services. If it is not done, then Indonesia is a "soft" market for other Asean countries because Indonesia has the largest population (population size) in ASEAN, which is no less than 270 million inhabitants. SMEs and Micro Enterprises, which are the embodiment of people's economic democracy, are devastated when the flow of goods and services so swiftly from various Asean Countries invades the Indonesian market. Realizing that doing empowering SMEs and Micro Enterprises is a necessity and a necessity to be able to find national identity that has comparative advantage and competitive advantage. This activity begins with identifying the existing problems and then finding a solution method, the method used is to provide training and assistance. The results that have been achieved are the existence of AA business capabilities that produce 10 (ten) additional additional new products which include: 1. Sus Fla; 2. Sus Fla Buah; 3. Sus Rogut; 4. Cum-cum; 5. Panada; 6. Layers; 7. Brown sugar steamed buns; 8. Bongko menthuk; 9. Risol mayo; and Sausage solo. In addition, Micro Business "AA" can improve its ability in the field of simple bookkeeping and business management. The existence of these outcomes is an indication of increased business empowerment.Keywords: Empowerment- Product Diversification- Cake.